Does moderate-intensity continuous training result in greater total energy expenditure compared to high-intensity interval training? - Vidal Andreato, L.; Magnani Branco, B. H.; Esteves, J. V. (Journal of Sports Sciences, 2019)
Recently in the Journal of Sports Sciences, Schaun et al. published a study on the comparison of energy expenditure between high-intensity interval training and moderate continuous training performed in water. With this Letter to the Editor, the authors would like to comment on the methodological aspects that should be considered to analyze the results presented, as well as the conclusions.